2022
DOI: 10.3847/1538-4357/ac86c6
|View full text |Cite
|
Sign up to set email alerts
|

A Multiepoch X-Ray Study of the Nearby Seyfert 2 Galaxy NGC 7479: Linking Column Density Variability to the Torus Geometry

Abstract: Active galactic nuclei are powered by accreting supermassive black holes, surrounded by a torus of obscuring material. Recent studies have shown how the torus structure, formerly thought to be homogeneous, appears to be “patchy”: the detection of variability in the line-of-sight hydrogen column density, in fact, matches the description of an obscurer with a complex structure made of clouds with different column density. In this work, we perform a multiepoch analysis of the X-ray spectra of the Seyfert 2 galaxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Recent mid-infrared results (Leftley et al 2021) found evidence of the presence of polar warm dust at a distance r 1.5 pc, which is consistent with this scenario. The outer layer would also be clumpy, allowing for the observed long-term variability, a similar scenario to the one proposed for NGC 7479 by Pizzetti et al (2022).…”
Section: Ionized Absorberssupporting
confidence: 60%
See 1 more Smart Citation
“…Recent mid-infrared results (Leftley et al 2021) found evidence of the presence of polar warm dust at a distance r 1.5 pc, which is consistent with this scenario. The outer layer would also be clumpy, allowing for the observed long-term variability, a similar scenario to the one proposed for NGC 7479 by Pizzetti et al (2022).…”
Section: Ionized Absorberssupporting
confidence: 60%
“…In particular, in some cases the X-ray absorbing medium is variable on very short timescales (days/weeks), which implies that the obscuring medium is clumpy and located at much smaller distances than the torus, possibly consistent with the BLR (e.g., Risaliti et al 2007;Bianchi et al 2009;Maiolino et al 2010;Sanfrutos et al 2013;Marinucci et al 2013;Walton et al 2014). In other cases, the X-ray absorption variability timescale is of the order of months or years (e.g., Piconcelli et al 2007;Rivers et al 2011;Coffey et al 2014;Rivers et al 2015;Ricci et al 2016;Pizzetti et al 2022), suggesting an origin from the putative circumnuclear torus. However, these results strongly depend on the observation sampling time; frequently adopted monthly observational monitoring may lose the variations at lower timescales.…”
Section: Introductionmentioning
confidence: 99%
“…measurements when a source has multiepoch observations. This has been proven in recent works on sources such as NGC 7479 (Pizzetti et al 2022), NGC 1358 (Marchesi et al accepted), and in a sample of Compton-thin (Zhao et al 2021) and Compton-thick (N. Torres-Albà 2022, in preparation) sources. The three obscured AGN in our sample 9 (i.e., excluding 2MASX J02051994 −0233055) all lie away from the diagonal dashed line, thus further supporting this hypothesis.…”
Section: Observational Evidence For Nonhomogeneity Of the Obscuring M...mentioning
confidence: 56%
“…We note that while some AGN have shown line-of-sight N H variability (see, e.g., Risaliti et al 2010;Markowitz et al 2014;Laha et al 2020;Pizzetti et al 2022), no source has yet varied from a Compton-thick AGN state to an unobscured one. Therefore, it is much more likely that intrinsic luminosity variability is responsible for the change in spectral shape of 2MASX J02051994−0233055, as is supported statistically by our fits.…”
Section: Comparison With Previous Resultsmentioning
confidence: 86%
“…In particular, in some cases, the X-ray absorbing medium is variable on relatively very short timescales (days to weeks), which implies that the obscuring medium is clumpy and located at much smaller distances than the torus, possibly consistent with the BLR (e.g., Risaliti et al 2007;Bianchi et al 2009;Maiolino et al 2010;Sanfrutos et al 2013;Marinucci et al 2013;Walton et al 2014). In other cases, the X-ray absorption variability timescale is of the order of months or years (e.g., Piconcelli et al 2007;Rivers et al 2011Rivers et al , 2015Coffey et al 2014;Ricci et al 2016;Pizzetti et al 2022), suggesting an origin from the putative circumnuclear torus. However, these results strongly depend on the observation sampling time; frequently adopted monthly observational monitoring may lose the variations at lower timescales.…”
Section: Introductionmentioning
confidence: 99%